PENGARUH RISIKO LITIGASI DAN CORPORATE GOVERNANCE TERHADAP KEBERADAAN AHLI AKUNTANSI DALAM KOMITE AUDIT - Saesar Adhidewanto; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2013)
The purpose of this study is to examine association betweeen litigation risk and corporate governance mechanisms consisting of the ownership of controlling shareholders, foreign ownership, government ownership, board size, the size of board commissioners, independent commissioners, capital adequacy ratio (CAR) and the external auditor Big 4 with the proportion of accounting financial experts within banking firm’s audit committee. Based on purposive sampling method, 69 banking firms which consistently have been listing in Indonesia Stock Exchange (BEI) from 2009-2011 are obtained. The data was analyzed with classic assumption test and the hypotheses were examined using linear regression model. The result of this study provides evidence that litigation risk which is considered as external factor and independent commissioners as a part of corporate governance mechanisms significantly associated with proportion of accounting financial experts within banking firm’s audit committee. However, the other corporate governance mechanisms which are the ownership of controlling shareholders, foreign ownership, government ownership, board size, the size of board commissioners, capital adequacy ratio (CAR) and the external auditor Big 4 have no significant association with proportion of accounting financial experts within audit committee.